On the Way to the Web: The Secret History of the Internet and Its Founders - Banks, Michael A. (Apress, 2012)
Friday was a good day to be indoors and online. It was the middle of a long holiday weekend, with temperatures hovering in the high nineties. Chat rooms buzzed with untold thousands of conversations on everything from television and the stock market to computers and, of course, the weather. Stubborn gamers engaged in mortal multiplayer combat literally clogged some parts of the Internet, while shoppers flooded online malls like lemmings. Online auctions offered the possibility of bargains on hot items like the new Sony Walkman.iption= HTTP